The ama handbook of project management (Amacom, 2006)
The book’s editors—Paul Dinsmore and Jeannette Cabanis-Brewin—should be commended for doing an excellent editorial job….[the editorial effort] is particularly significant in view of the fact that this handbook comprises work written by 42 distinct authors….All chapters are informative and well written….its objective it to put project management into its contemporary context, enabling readers to get up to speed on important issues in project management today. In my view, the book has done a fine job in achieving this objective